2019
DOI: 10.1063/1.5078575
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature multiferroicity and magnetoelectric coupling in Na-deficient sodium bismuth titanate

Abstract: Herein, we report a Na deficient single phase sodium bismuth titanate perovskite exhibiting ferromagnetism with reduced leakage conductivity and a self-biased high magnetoelectric (ME) coupling coefficient at room temperature (27 °C). Observed ferromagnetism is induced by sodium cation vacancy dominated by spin polarization of holes in the valence band. An unexpected high ME coupling coefficient of about 4.18 mV/cm Oe, observed at zero DC magnetic bias field, is relatively large and juxtapose to other single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Reproduced with permission from [28]. Ruth et al [29] reported lead-free Na-deficient single-phase sodium bismuth titanate perovskite Na0.42Bi0.52Ti1.005O 3 ferroelectrics. The material has shown a self-bias ME coefficient around 4.18 mV•cm −1 •Oe −1 (H AC = 1 Oe at 1 kHz) at zero DC magnetic field and room temperature [29].…”
Section: Single-phase Mementioning
confidence: 99%
“…Reproduced with permission from [28]. Ruth et al [29] reported lead-free Na-deficient single-phase sodium bismuth titanate perovskite Na0.42Bi0.52Ti1.005O 3 ferroelectrics. The material has shown a self-bias ME coefficient around 4.18 mV•cm −1 •Oe −1 (H AC = 1 Oe at 1 kHz) at zero DC magnetic field and room temperature [29].…”
Section: Single-phase Mementioning
confidence: 99%